The ruling coalitions in the Republic of Moldova after the “Twitter Revolution” – the policy of integration or desintegration? - Sikora-Gaca, Małgorzata (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2018)
In 2009, the Republic of Moldova created an alternative to the communist leadership. In 2013, the Alliance for European Integration was replaced by the Alliance for Pro-European Governance, which secured two issues: the signing of the Association Agreement between the Republic of Moldova and the European Union, and the interests of local oligarchs. After the parliamentary elections in 2014, as an alternative to the increasingly powerful Igor Dodon’s Party of Socialists, another coalition, the Political Alliance for European Moldova was created and ‘sealed’ by embezzling 1 billion from Moldovan banks (12.5% of GDP). The coalition formed in January 2015, was replaced by the re-launched Alliance for European Integration, and then by another coalition without a definite name in January 2016. This extremely expanded political activity is a backdrop for the façade of democracy and the subsequent parliamentary elections scheduled for 2018. The pro-European coalitions in the Republic of Moldova discredited themselves in front of the society as strongly as their predecessors (the communists), causing a state of general disintegration.